Toward More Impactful International Business Education : A Teaching Innovation Typology - Dieleman, Marleen; Šilenskytė, Aušrinė; Lynden, Karen; Fletcher, Margaret; Panina, Daria (Taylor & Francis, 2022)
Teaching innovations in the field of higher education (HE) have the potential to lead to better learning outcomes and higher faculty motivation. While the pedagogy literature has explored different types of teaching innovations, International Business (IB) scholars have paid relatively little attention to how these innovations are disseminated and generate impact across the IB field. This paper addresses this gap. Drawing on the innovation literature in management and the pedagogy literature on teaching innovations, we provide a typology of teaching innovations and their impact in the context of IB education. This framework illustrates the spread of teaching innovations by considering the intersection of types of pedagogy innovations, and the stakeholders impacted by them. By introducing this framework and illustrating select IB teaching innovations, we contribute to the pedagogy literature in the IB field. The framework also offers practical guidance for innovative educators and HE institutions.
Keywords: higher education; International business; teaching impact; teaching innovation; teaching innovation dissemination; higher education (teaching); pedagogy; fi=Strateginen johtaminen|en=Strategic Management|